Strategic Scientific Disclosure: Evidence from the Leahy–Smith America Invents Act - VALENTINE, KRISTEN; ZHANG, JENNY LI; ZHENG, YUXIANG (Journal of Accounting Research, 2025)
ABSTRACT We examine the impact of technological competition on voluntary innovation disclosure around the enactment of the Leahy–Smith America Invents Act of 2011 (“AIA”). The AIA moves the US patent system from the first‐to‐invent to first‐inventor‐to‐file system and induces a patent race that increases technological competition. Firms that are slow to file a patent are disadvantaged in this race. We find that focal firms with lagging patent classes strategically increase scientific publications in their lagging technology areas in an attempt to block competitors from obtaining a patent. This effect is more pronounced in technology areas where the firm has better information about their relative competitive position (proxied by greater inventor mobility), in technology classes with constraints on increasing patent filing timeliness (proxied by fewer experienced attorneys), and areas characterized by more intense competition. We find that the peers of firms with lagging classes experience greater patent filing rejections for lack of novelty and obviousness reasons after the AIA, suggesting that strategic scientific disclosure is effective.